Harmoni dalam Keberagaman: Analisis Tradisi Kopral Kasemo di Desa Tanon Kediri - M. Kharis Majid; Muttaqin; Syadza Nayma Seyobudi; Shafa Nayla Seyobudi; Hubbana Ya Muji Bassailin (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2026)
The Kopral Kasemo tradition in Tanon Village, Papar, Kediri, is a local tradition that brings together people from different faiths in a communal prayer ritual to commemorate the heroes of the independence struggle. This research is motivated by the limited research on local traditions as models of culture-based tolerance in a multicultural society. This study aims to analyze the role of the Kopral Kasemo tradition in building tolerance and social harmony between religious communities in Tanon Village. The study employed a descriptive qualitative approach, with data collection techniques including in-depth interviews, observation, and documentation. The informants included community leaders, village officials, migrants, and native residents of Tanon Village. Data were analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results show that the Kopral Kasemo tradition not only serves as a form of respect for heroes but also serves as a medium for social interaction and active tolerance practices among Muslims, Hindus, and Catholics. The values ​​of mutual cooperation, social solidarity, and respect for differences are embodied through community involvement in the entire series of traditions. This research confirms that local culture can be an effective instrument in strengthening social cohesion and building harmony in a multicultural society. These findings contribute to the development of multicultural sociological studies, particularly regarding the role of local traditions in maintaining tolerance and harmony between religious communities.